Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea) - Ng, Peter K. L.; Castro, Peter (Zootaxa, 2016)
The family Chasmocarcinidae Serène, 1964, is revised based on the examination of the type material of many of its species as well as unidentified and previously identified material from around the world. The revised family now consists of three subfamilies comprising 16 genera (including eight described as new) and 51 species (including 19 described as new). The subfamily Chasmocarciinae Serène, 1964, consists of Amboplax n. gen. with one species; Angustopelta n. gen. with four species, two of which are new; Camatopsis Alcock & Anderson, 1899, with six species, five of which are new; Chasmocarcinops Alcock, 1900, with one species; Chasmocarcinus Rathbun, 1898, with 11 species, one of which is new; Chinommatia n. gen. with five species, two of which are new; Deltopelta n. gen. with one species; Hephthopelta Alcock, 1899, with two species, one of which is new; Microtopsis Komai, Ng & Yamada, 2012, with two species, one of which is new; Notopelta n. gen. with one species; Statommatia n. gen. with five species, two of which are new; and Tenagopelta n. gen. with three species, two of which are new. The subfamily Megaesthesiinae Števčić, 2005, consists of Alainthesius n. gen. with two species, both of which are new; Megaesthesius Rathbun, 1909, with four species, one of which is new. The subfamily Trogloplacinae Guinot, 1986, consists of Australocarcinus Davie, 1988, with three species, and Trogloplax Guinot, 1986, with one species. A neotype is selected for Chasmocarcinus cylindricus Rathbun, 1901. Three nominal species were found to be junior subjective synonyms of other species: Chasmocarcinus panamensis Serène, 1964, of C. longipes Garth, 1940; Chasmocarcinus rathbuni Bouvier, 1917, of C. typicus Rathbun, 1898; and Hephthopelta superba Boone, 1927, of Deltopelta obliqua (Rathbun, 1898). Thirteen chasmocarcinid genera are exclusively found in the Indo-West Pacific region, one (Chasmocarcinus) in both the Western Atlantic and Tropical Eastern Pacific regions, and two (Deltopelta n. gen. and Amboplax n. gen.) exclusively in the Western Atlantic. Chasmocarcinids are remarkable for occurring from depths exceeding 1000 m to shallow water and completely freshwater habitats: chasmocarcinines and megaesthesiines are found from shallow to deep water marine ecosystems, whereas trogloplacines live in freshwater streams, including cave systems.